Analysis of factors influencing yield variability of major crops in China - Guo L; Andreas W; Yu HY; Xiu JC (2013)
The objective of this research was to analyze the characteristics and major factors influencing yield variability of a number of major crops in China from 1981 to 2010. Based on data for yield and sown area of a crop, four methods were used to separate crop trend yield and meteorological yield from actual yield. There was an association between total yield and per unit area yield for all major crops over the past 30 years in China. The per unit area yields of fruits increased more rapidly than other crops, and was about 7.09% for citrus fruit annually. The trend yield for different crops also increased year by year. However, meteorological yield fluctuated greatly with greatest fluctuations occurring for fruits (17.76% for citrus and 15.83% for apple). The contributions of sown area and per unit area yield to variability of total yield varied among the major crops. For grains and fruits, the contribution of per unit area yield had the dominant effect, while the opposite was the case for sugar crops and cotton. For oil crops both factors contributed almost equally. The variability in per unit area yield of all crops could be largely attributed to variability of meteorological factors. Social factors, such as agricultural policy and improved technology, played relatively lesser roles. The four methods used in the analysis showed no significant differences. The contributions of the above factors to yield variability were species dependent. To ensure agricultural production security, more attention should be paid to enhance the per unit area yield of crops together with the impact of climate change on yields.